Effect of uphill and downhill walking on walking performance in geriatric patients using a wheeled walker - Lindemann, Ulrich; Schwenk, Michael (Zeitschrift für Gerontologie und Geriatrie, 2017)
BACKGROUND: Wheeled walkers are recommended to improve walking performance in older persons and to encourage and assist participation in daily life. Nevertheless, using a wheeled walker can cause serious problems in the natural environment. This study aimed to compare uphill and downhill walking with walking level in geriatric patients using a wheeled walker. Furthermore, we investigated the effect of using a wheeled walker with respect to dual tasking when walking level.
Published online: 22 November 2016
Gesehen am 14.08.2017